MERAWAT BUDAYA LOKAL DI ERA GLOBALISASI (UPAYA PENDIDIKAN ISLAM DALAM MERAWAT BUDAYA LOKAL) - Agus Salim Salabi (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2020)
Local culture is something that is bound and related to places, regions, and physical things such as geography. Like Javanese culture, of course it will develop in the Java area, Batak culture, Banjar culture as well as other cultures. Globalization can be defined as the process of making everything one earth or one world. Globalization can bring positive things such as: feeling ease, comfort, beauty, and progress. Besides that, it can also present negative things such as: causing suffering, anxiety, and misdirection. This research uses a case study approach, with a type of qualitative research.